Factors Influencing The Psychological Well-Being of Street Venodrs in Hpa-An Township, Karen State, Myanmar: A Path Analytic Study - Lar Aye, Nan She; Varma, Parvathy (Scholar: Human Sciences, 2016)
The present study examined the factors that influence the psychological well-being among street vendors in and around the public markets of Hpa-an township, Karen State, Myanmar. A total of 190 female participants who make a living as street vendors in the local markets were obtained by convenience sampling method. The findings of this study revealed that the vendors reported having average levels family functioning, social support, stress, and psychological well-being, used average levels of coping styles. The results showed that the vendors’ social support has direct and positive influence on their psychological well-being. Moreover, the findings yielded direct and positive influences of family functioning, problemfocused coping, and emotion-focused coping on their level of stress. Regardless of having healthy relationships in the family and employing two types of coping strategies, these vendors still reported experiencing certain levels of stress. It is evident that these vendors certainly need professional advice and guidance in order to deal with various stressors in their daily lives.